2020
DOI: 10.1002/btm2.10182
|View full text |Cite
|
Sign up to set email alerts
|

Resection and survival data from a clinical trial of glioblastoma multiforme‐specific IRDye800‐BBN fluorescence‐guided surgery

Abstract: Supra-maximum surgical tumor resection without neurological damage is highly valuable for treatment and prognosis of patients with glioblastoma multiforme (GBM). We developed a GBM-specific fluorescence probe using IRDye800CW (peak absorption/ emission, 778/795 nm) and bombesin (BBN), which (IRDye800-BBN) targets the gastrin-releasing peptide receptor, and evaluated the image-guided resection efficiency, sensitivity, specificity, and survivability. Twenty-nine patients with newly diagnosed GBM were enrolled. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Two studies have used a different approach to visualizing BnRs on gliomas by forming fluorescence BnR-conjugated PET ligands, which can be used preoperatively or at surgery (173,174). The BnR ligand 68 Ga-IRDye800CW-BBN is a PET/near-infrared fluorescence (NIRF) dual-imaging modality GRPR ligand developed to fulfil these two requirements.…”
Section: Bnr: Cns/neural Tumor Imaging: Studies In Literature: Gliomamentioning
confidence: 99%
“…Two studies have used a different approach to visualizing BnRs on gliomas by forming fluorescence BnR-conjugated PET ligands, which can be used preoperatively or at surgery (173,174). The BnR ligand 68 Ga-IRDye800CW-BBN is a PET/near-infrared fluorescence (NIRF) dual-imaging modality GRPR ligand developed to fulfil these two requirements.…”
Section: Bnr: Cns/neural Tumor Imaging: Studies In Literature: Gliomamentioning
confidence: 99%
“…Of note, the authors reported that the approach was not optimal for deep-seated tumors as signal-tobackground ratios were not adequate during surgery in some instances. In another study, He et al (53) investigated the extent of resection and survivability using BBN-IRdye800CW in 29 patients. To avoid confounding variability due to inter-surgeon differences, all procedures were performed by the same surgeon.…”
Section: Bbn-irdye800cw (Peptide)mentioning
confidence: 99%
“…Intraoperative glioblastoma multiforme imaging with 1 mg total BBN-IRdye800CW administered 16 h prior to surgery: NIRF prior to resection (B) , residual fluorescence after initial tumor removal (C) and tumor-cavity after complete resection (D) . Panels (B–D) are adapted from ( 53 ) with permission.…”
Section: Bbn-irdye800cw (Peptide)mentioning
confidence: 99%
See 1 more Smart Citation
“…Using fluorescence-guided resection, no tumor regrowth was observed compared to resection performed under bright light. The efficacy of fluorescence-guided resection has also been observed in several clinical trials, underscoring the need for a single compound that could potentially be used for diagnostic, guided surgery and post-surgical assessment [ 136 , 137 ]. Another advantage of fluorescence in cancer management resides in the use of tracer’s emission for intraoperative frozen section histology, which consists in imaging resected tissue sections during surgery to assess if tumorous tissues are remaining [ 138 ].…”
Section: Applicationsmentioning
confidence: 99%